2004
DOI: 10.1007/s11102-005-4024-6
|View full text |Cite
|
Sign up to set email alerts
|

Subclinical Cushing's Syndrome

Abstract: Subclinical Cushing's syndrome (CS) is attracting increasing interest since the serendipitous discovery of an adrenal mass has become a rather frequent event owing to the routine use of sophisticated radiologic techniques. Cortical adenoma is the most frequent type of adrenal incidentaloma accounting for approximately 50% of cases in surgical series and even greater shares in medical series. Incidentally discovered adrenal adenomas may secrete cortisol in an autonomous manner that is not fully restrained by pi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
51
1
12

Year Published

2006
2006
2015
2015

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 81 publications
(66 citation statements)
references
References 67 publications
2
51
1
12
Order By: Relevance
“…The delayed diagnosis of SH could impact negatively on morbidity and the identification of patients with SH may suggest in some of them the need of adrenalectomy, which has been shown to ameliorate cardiovascular risk profile of these patients (30,31).…”
Section: Discussionmentioning
confidence: 99%
“…The delayed diagnosis of SH could impact negatively on morbidity and the identification of patients with SH may suggest in some of them the need of adrenalectomy, which has been shown to ameliorate cardiovascular risk profile of these patients (30,31).…”
Section: Discussionmentioning
confidence: 99%
“…Among patients with adrenocortical adenomas, those with no typical symptoms of Cushing's syndrome (CS) such as moon face, buffalo hump etc. but showing the autonomous secretion of cortisol have been identified as having preclinical (or subclinical) Cushing's syndrome [20,21]. Although the concept of preclinical (or subclinical) CS is not universally accepted [14], Spath et al recently reported that we should consider an APA with co-secretion of cortisol if a patient has 1) PA and an adenoma that is larger than 2.5 cm, 2) cortisol that is non-suppressible with overnight low-dose dexamethasone, or 3) grossly elevated serum levels of hybrid steroids, such as 18-OH-F [22].…”
Section: Expression Of Steroidogenic Enzymes and Kcnj5 Mrna In Patienmentioning
confidence: 99%
“…However, in about 5-30% of patients, endocrine work-up reveals abnormalities of the hypothalamic-pituitary-adrenal (HPA) axis function, in keeping with a subtle cortisol hypersecretion, defined as 'subclinical Cushing's syndrome' or 'subclinical hypercortisolism' (SH) (7,8). The true SH prevalence is unknown, due to the lack of widely accepted biochemical criteria for defining this condition (7)(8)(9)(10)(11).…”
Section: Introductionmentioning
confidence: 99%